Chemical circularization of in vitro transcribed RNA for exploring circular mRNA design - Malgorzata Wasinska-Kalwa; Adam Mamot; Karol Czubak; Katarzyna Frankowska; Adam Ado Rajkiewicz; Tomasz Spiewla; Marcin Warminski; Zofia Pilch; Marta Szulc-Gasiorowska; Kacper Siekan; Andrzej Dziembowski; Dominika Nowis; et al. (Nature Communications)
Abstract Circularization is an important step for therapeutic messenger RNA (mRNA) enhancements. Current enzymatic and ribozymatic-based circularization methods face limitations including sequence constraints, purification challenges, and sub-optimal biological activity. Chemical strategies, while promising, have been restricted to short RNA sequences. Here, we report a method for chemically circularized in vitro transcribed RNAs of various lengths (chem-circRNAs; 35–4000 nt) with circularization efficiencies reaching up to 60%. This approach leverages a 5′ ethylenediamine modification and a periodate-oxidized 3′ end to drive intramolecular reductive amination. We demonstrate that this method is applicable to various sequences and modification compatible. We report the effective separation methods of chem-circRNAs from their linear precursors. We show that protein-coding chem-circRNAs are translationally active in cells and exhibit increased durability, like enzymatically circularized mRNAs. Furthermore, our method allows incorporation of functional modifications, including endocyclic N7-methylguanosine cap and N1-methylpseudouridine, enabling access to chemically defined translationally active circRNAs for therapeutic applications.